Effect of palliative care decisions making on hospital service use at end-of-life in patients with malignant brain tumors: a retrospective study - Nåhls Nelli-Sofia; Leskelä Riikka-Leena; Saarto Tiina; Hirvonen Outi; Anttonen Anu (BMC, 2025)
Background: Palliative care (PC) improves Quality of life and reduces the symptom burden. Aggressive treatments at end of life (EOL) postpone PC. The aim of this single-center retrospective study was to evaluate the timing of the PC decision i.e., termination of cancer-specific treatments and focusing on symptom-centered PC, and its impact on the use of tertiary hospital services at the EOL.
Methods: A retrospective cohort study on brain tumor patients, who were treated at the Comprehensive Cancer Center of the Helsinki University Hospital from November 1993 to December 2014 and died between January 2013 and December 2014, were retrospectively reviewed. The analysis comprised 121 patients (76 glioblastoma multiforme, 74 males; mean age 62 years; range 26-89). The decision for PC, emergency department (ED) visits and hospitalizations were collected from hospital records.
Results: The PC decision was made for 78% of the patients. The median survival after diagnosis was 16 months (13 months patients with glioblastoma), and after the PC decision, it was 44 days (range 1-293). 31% of the patients received anticancer treatments within 30 days and 17% within the last 14 day before death. 22% of the patients visited an ED, and 17% were hospitalized during the last 30 days of life. Of the patients who had a PC decision made more than 30 days prior to death, only 4% visited an ED or were hospitalized in a tertiary hospital in the last 30 days of life compared to patients with a late (< 30 days prior to death) or no PC decision (25 patients, 36%).
Conclusions: Every third patient with malignant brain tumors had anticancer treatments during the last month of life with a significant number of ED visits and hospitalizations. Postponing the PC decision to the last month of life increases the risk of tertiary hospital resource use at EOL.